Pandemics, privacy, and public health research - Bernier, Alexander (Can J Public Health, 2020)
Sharing data expediently for pandemic response purposes exposes healthcare providers in Canada to significant regulatory uncertainty. Duplicative and contradictory ethical and legal duties flowing from overlapping sources can stifle flows of medical data among clinicians, researchers, and institutions. Authorities should support caregivers and accelerate research by providing clear guidance to the health sector. Institutions should foster robust data stewardship and standardize their practices to those recognized among the international health informatics community. Reform is critical to ensuring Canadian healthcare providers can deliver efficient health responses that are integrated with dispersed and disparate national and international approaches.